2022
DOI: 10.3389/fmed.2022.799544
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as an Independent Risk Factor for Depression in Patients With End-Stage Renal Disease: A Cross-Sectional Study

Abstract: BackgroundDepression confers substantial disease burden globally, especially among those with chronic kidney disease (CKD). The presence of depression significantly impairs one's quality of life. Risk factors for depression in patients with CKD remain under-appreciated, and whether frailty, a geriatric phenotype, constitutes a risk factor for depression in this population is unknown.MethodsWe prospectively enrolled patients with end-stage renal disease (ESRD) undergoing hemodialysis for >3 months from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…In a cross-sectional study involving 80 patients on hemodialysis, patients suffering from depression were 9.8 times more likely to be frail than were patients without depression (odds ratio, OR = 9.80; 95% confidence interval, CI, 1.93-49.79) [ 45 ]. In addition, frailty was found to be an independent risk factor for developing depression in this population: there is thus a linear relation between a greater frailty severity and the probability of depression [ 46 ]. Frailty and sarcopenia were also found to be associated with increased risks of falls, hospitalization, institutionalization, and mortality [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study involving 80 patients on hemodialysis, patients suffering from depression were 9.8 times more likely to be frail than were patients without depression (odds ratio, OR = 9.80; 95% confidence interval, CI, 1.93-49.79) [ 45 ]. In addition, frailty was found to be an independent risk factor for developing depression in this population: there is thus a linear relation between a greater frailty severity and the probability of depression [ 46 ]. Frailty and sarcopenia were also found to be associated with increased risks of falls, hospitalization, institutionalization, and mortality [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…FRAIL scale was coined since 2012 as an easy-to-administer instrument for identifying frail adults, and its results exhibited excellent correlation with those using the Fried's criteria [16] and other instruments [17]. Individuals with FRAIL-detected frailty (≥3 positive components) had an increased risk of mortality, disability, fall, institutionalization, and other geriatric syndrome development compared to robust ones [18][19][20]. FRAIL scale has been validated for its applicability in younger populations, including those with morbidities such as CKD or DM [21].…”
Section: Outcome Definitionmentioning
confidence: 99%
“…For instance, a population‐based study showed that severe frailty increased the risk of urolithiasis by 23%–46% 19 and increased the probability of dysnatremia, hypokalemia, and hypophosphatemia by 15%–52% 20 . The presence of frailty aggravates vital organ damage by raising the likelihood of kidney function decline, 21 depression, 22 and cognitive impairment 23 among those with diabetes mellitus (DM) or chronic kidney disease (CKD). Frailty may compound the host's suboptimal health by setting the stage for metabolic syndrome 24 and body fat redistribution 25 .…”
Section: Frailty: An Introductory Overviewmentioning
confidence: 99%